Leadership and Employee Performance in Digital Transformation: A Systematic Review (2020–2025) - Syupriadin Syupriadin; Winda Dewi Listyasari; Linda Ika Mayasari; Kamaludin Kamaludin (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study investigates how research on Leadership and employee performance has evolved within the digital transformation landscape through a Systematic Literature Review (SLR) of publications from 2020 to 2025. The literature search was conducted in Scopus and Google Scholar using the Publish or Perish tool, with search terms including “Leadership," "digital transformation," and "employee performance." The review adhered to the PRISMA framework, which comprises sequential phases: identifying relevant studies, screening titles and abstracts, assessing eligibility, and determining final inclusion. Of 500 initial publications, 30 met all criteria and were analysed comprehensively. The synthesis reveals that both transformational and digital Leadership consistently contribute positively to outcomes such as employee performance, motivation, innovation, and adaptability. The bibliometric results further indicate three dominant thematic groupings: digital Leadership, employee performance, and organisational responses to technological change. Overall, the evidence underscores that effective digital transformation requires not only technological infrastructure but also competent human resources and Leadership approaches that support organisational change. This review enriches theoretical understanding of current research patterns and offers practical guidance for enhancing Leadership capability and human resource development in the digital era.